Response of corn Zea mays L. to combinations of organic fertilization and spraying with potassium nanoparticles in some yield characteristics (Journal of Pharmaceutical Negative Results, 2022)
A field experiment was conducted in one of the fields of Ibn Al-Bitar Preparatory Vocational School - Holy Kerbala Governorate for the spring season 2021, to know the effect of different sources of organic matter and spraying with potassium nanoparticleson yield of corn Zea mays L..Randomized Complete Block Design (RCBD) with three replications was used to setup this study. The study included two factors, first factors was the combinations of organic fertilizers:{control, 2000kg ha-1 cows, 2000kg ha-1Poultry}, 1500 kg ha-1cows + 500kg ha-1 poultry, 1000 kg ha-1 cows +1000 kg ha-1 poultry and 1750 kg ha-1 cows + 250 kg ha -1 poultry . the Second factor was spraying with nano-potassium {0,1000 mg L-1 and 2000 mg L-1} .data were statistically analyzed and the averages were compared according to the least significant difference at the 5% probability level. The results showed that the treatment T5 {1750 kg ha-1 cows + 250 kg ha-1 poultry} was a significantly exceeded in all studied traits. the concentration of potassium nanoparticals {2000 mg L-1} was superior to give highest values in all characteristics under study.We conclude from this study that the integrated application of combinations of organic fertilization and spraying with potassium nanoparticles is more effective in improving yield of corn.